Functional characterization of chalcone reductase gene CHR3 through RNAi (Bangladesh Journal of Botany, 2024)
In this experiment, the soybean genome "Jilin 30" was used as a template to clone the target gene CHR3 using specific primers. The sense fragment, antisense fragment, and intron of the target gene were ligated into pCAMBIA3300 through double enzyme digestion to form a stem loop structure. We then transferred the constructed RNAi vector pCAMBIA3301-CHR3 RNAi into the recipient soybean genome via Agrobacterium mediated method, specifically reducing the expression of the target gene CHR3. By genetic transformation, positive plants were obtained, and molecular biology methods such as Southern blotting, real-time quantitative PCR, isoliquiritigenin analysis, and identification of resistance to Phytophthora root rot were used to detect the expression level of the CHR3 gene in the positive plants and study its function.The RNAi expression vector pCAMBIA3300-CHR3-RNAi was successfully constructed using the sense and antisense fragments of 428 bp CHR3 gene and an intron of 110 bp was inserted to form the stem-loop structure of the RNAi vector. PCR was used to detect 6 lines of the T1 generation and 15 lines of the T2 generation. The results of Southern analysis confirmed the integration of  CHR3 and marker genes  into the soybean genome. The expression CHR3 gene in the T1 genotypes decreased by 13.1 to 58.3%; the expression in the root decreased by 0.9 to 47.4%; the expression in the leaf decreased by 20 to 44.2%; and the expression in the stem decreased by 7.6 to 23%. The content of isoliquiritigenin decreased by 26.7% as transgenic shoots had a lower content of isoliquiritigenin and reduced resistance to Phytophthora sojae.Bangladesh J. Bot. 53(3): 627-633, 2024 (September) Special